All-solid-state battery cell, preparation method thereof and all-solid-state battery

By coating electrolyte slurry on the two-sided surface of the lithium foil and laminating it alternately with the positive electrode sheet, the problem of insufficient mechanical strength of the solid electrolyte membrane of the all-solid state battery is solved, and efficient production and compatibility with the liquid battery production line is achieved.

CN119419370APending Publication Date: 2025-02-11GAC AION NEW ENERGY AUTOMOBILE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411575967.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

Due to insufficient mechanical strength of the solid electrolyte membrane, it is difficult to directly wind the laminate, resulting in low production efficiency and incompatible with existing liquid battery production lines.

Method used

The electrolyte slurry is directly coated on the two-sided surface of the lithium foil to form a solid electrolyte layer, and alternately stacked with the positive electrode sheet, and an all-solid battery cell is obtained by isostatic pressure treatment.

Benefits of technology

It effectively solves the problem of poor mechanical properties of the solid electrolyte layer, simplifies the production process, improves production efficiency, and makes all-solid-state batteries compatible with liquid battery production lines.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119419370A_ABST
    Figure CN119419370A_ABST
Patent Text Reader

Abstract

The invention relates to an all-solid-state battery cell, a preparation method thereof and an all-solid-state battery, and belongs to the technical field of all-solid-state batteries. The preparation method comprises the following steps: respectively coating two opposite side surfaces of a positive current collector with positive slurry to form a positive active layer and obtain a positive plate; the method comprises the following steps: respectively coating electrolyte slurry on two opposite side surfaces of a lithium foil in a protective atmosphere to form a solid electrolyte layer and obtain an electrolyte / lithium foil / electrolyte composite sheet; and alternately laminating the positive plate and the electrolyte / lithium foil / electrolyte composite sheet to form an intermediate, and carrying out isostatic pressing treatment on the intermediate to obtain the all-solid-state battery cell. The electrolyte / lithium foil / electrolyte composite sheet is obtained by directly forming the solid electrolyte layer on the surface of the lithium foil, the positive plate is obtained by combining and simultaneously forming the positive active layer on the surface of the positive current collector, and only one-time isostatic pressing treatment is needed after alternate lamination, so that the production process of the all-solid-state battery can be greatly simplified, and the production efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of all-solid-state batteries, and in particular to an all-solid-state battery cell and a preparation method thereof, and an all-solid-state battery. Background Art

[0002] During the design and manufacturing process of all-solid-state batteries, the poor mechanical strength of the solid electrolyte membrane makes it difficult to directly wind and stack it like the diaphragm used in liquid batteries. This results in low production efficiency of solid-state batteries and incompatibility with the currently industrialized liquid battery production line. In most existing studies, the mechanical strength of the solid electrolyte membrane is usually improved by improving the binder, or by coating the support and then transferring it. The former has little improvement effect in the final winding film forming step, and the latter requires the support to be removed after transfer, which obviously complicates the process equipment. Therefore, improving the production efficiency of all-solid-state batteries and simplifying the production process of all-solid-state batteries are currently the research focuses in the design and development of all-solid-state batteries. Summary of the invention

[0003] To solve the above problems, the purpose of the embodiments of the present application includes providing an all-solid-state battery cell and a preparation method thereof and an all-solid-state battery, which can greatly simplify the production process of the all-solid-state battery and effectively improve the production efficiency of the all-solid-state battery.

[0004] In a first aspect, the present application provides a method for preparing an all-solid-state battery cell, comprising the following steps:

[0005] The positive electrode slurry is coated on two opposite sides of the positive electrode current collector to form a positive electrode active layer to obtain a positive electrode sheet;

[0006] Under a protective atmosphere, coating electrolyte slurry on two opposite sides of the lithium foil respectively to form a solid electrolyte layer to obtain an electrolyte / lithium foil / electrolyte composite sheet;

[0007] The positive electrode sheets and the electrolyte / lithium foil / electrolyte composite sheets are alternately stacked to form an intermediate, and the intermediate is subjected to isostatic pressing to obtain an all-solid-state battery cell.

[0008] In the above technical scheme, by directly coating the electrolyte slurry on the double-sided surface of the lithium foil under a protective atmosphere to form a solid electrolyte layer, the problem that it is difficult to directly wind the laminate due to the poor mechanical properties of the solid electrolyte layer in the prior art can be effectively solved. Compared with coating the electrolyte slurry on the negative electrode current collector, lithium foil is used in this application, which not only acts as the negative electrode active material but also acts as the negative electrode current collector itself, that is, a "negative electrode-free battery" is formed, which is conducive to further improving production efficiency and simplifying the process flow. In addition, the positive electrode sheet is obtained by simultaneously combining the double-sided coating on the surface of the positive electrode current collector to form a positive electrode active layer, and the positive electrode sheet and the electrolyte / lithium foil / electrolyte composite sheet are alternately stacked. Only one isostatic pressing treatment is required to obtain a fully solid-state battery cell. Compared with the prior art, it can greatly simplify the production process, improve production efficiency, and solve the cost problem of compatibility with the currently industrialized liquid battery production line.

[0009] In some embodiments of the present application, the lithium foil is lithium metal or lithium alloy. Optionally, the thickness of the lithium foil is 20-100 μm.

[0010] In the above technical solution, the lithium foil used in the present application can be either lithium metal or lithium alloy, and can maintain stable performance under a protective atmosphere.

[0011] In some embodiments of the present application, the electrolyte slurry includes at least one of a sulfide electrolyte or a halide electrolyte.

[0012] Optionally, the solid electrolyte layer has a thickness of 25-70 μm.

[0013] In the above technical solution, since the mechanical strength of the solid electrolyte membrane does not need to be considered in this application, it can be applied to various types of solid electrolytes, and the thickness range of the solid electrolyte layer is relatively large, which is conducive to expanding the application scope of the technical solution of this application.

[0014] In some embodiments of the present application, the thickness of the positive electrode sheet is 85-200 μm.

[0015] In the above technical solution, the thickness range of the positive electrode sheet is relatively large and is fully compatible with the traditional liquid battery production line.

[0016] In some embodiments of the present application, before coating the electrolyte slurry on the two opposite surfaces of the lithium foil respectively, the method further includes: subjecting the lithium foil to a plasma activation treatment in a protective atmosphere.

[0017] In the above technical solution, lithium is an active metal and an oxide layer is easily formed on the surface of lithium foil. Therefore, it needs to be activated before use to remove the oxidized and degraded layer on the surface so as not to affect the electrochemical properties of the lithium foil.

[0018] In some embodiments of the present application, the alternating lamination steps are performed under a protective atmosphere.

[0019] Optionally, the protective atmosphere includes at least one of argon, nitrogen, helium, neon, krypton or xenon.

[0020] In the above technical solution, since the performance of lithium metal is very active, the alternating stacking steps are also carried out under a protective atmosphere, so that the assembly and production of lithium foil can be carried out in a protective atmosphere throughout the process, forming a fully protective gas production line, which can reduce dependence on the production line workshop environment and prevent oxidation and deterioration of lithium foil.

[0021] In some embodiments of the present application, the outermost layers on opposite sides of the intermediate body are positive electrode sheets;

[0022] Before isostatic pressing of the intermediate, it also includes:

[0023] An electrolyte / lithium foil composite sheet is arranged on the surface of the outermost positive electrode sheet of the intermediate body. The electrolyte / lithium foil composite sheet includes a stacked outer lithium foil and an outer solid electrolyte layer. A buffer material layer is arranged on the surface of the outer lithium foil away from the outer solid electrolyte layer.

[0024] In the above technical solution, in the present application, a single-layer solid electrolyte layer combined with a buffer material layer is used in the outermost layer of the all-solid-state battery cell, which can increase the safety of the battery while protecting the performance of the lithium foil.

[0025] In some embodiments of the present application, the buffer material layer includes at least one of a PEO film, a PEN film or a PPS film.

[0026] In the above technical solution, conventional battery cell coating materials, such as Mylar film, are incompatible with lithium metal. The above buffer material layers have good processability and mechanical strength, can resist the formation of lithium metal dendrites to a certain extent, are low in cost, do not react with lithium foil, have good thermal stability, and are well compatible, thus playing a good protective role for all-solid-state batteries, avoiding contact between the pole piece and the battery cell shell, and enhancing safety.

[0027] In a second aspect, an embodiment of the present application provides an all-solid-state battery cell prepared by the above-mentioned preparation method.

[0028] In a third aspect, an embodiment of the present application provides an all-solid-state battery comprising the above-mentioned all-solid-state battery cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0030] Figure 1 A schematic diagram of the structure of the positive electrode sheet provided in an embodiment of the present application;

[0031] Figure 2 A schematic diagram of the structure of the electrolyte / lithium foil / electrolyte composite sheet provided in an embodiment of the present application;

[0032] Figure 3 A schematic diagram of the structure of an intermediate obtained by alternately stacking a positive electrode sheet and an electrolyte / lithium foil / electrolyte composite sheet provided in an embodiment of the present application;

[0033] Figure 4 A schematic diagram of the structure of an all-solid-state battery cell provided in an embodiment of the present application;

[0034] Figure 5 A simplified process flow chart of the method for preparing an all-solid-state battery cell provided in an embodiment of the present application.

[0035] Description of reference numerals:

[0036] 100-positive electrode sheet; 10-positive electrode current collector; 12-positive electrode active layer; 200-electrolyte / lithium foil / electrolyte composite sheet; 20-lithium foil; 22-solid electrolyte layer; 300-intermediate; 30-electrolyte / lithium foil composite sheet; 32-buffer material layer; 40-battery cell casing; 400-all-solid-state battery cell. DETAILED DESCRIPTION

[0037] Figures 1 to 5 This is a process flow chart of the method for preparing the all-solid-state battery cell provided in the embodiment of the present application. Figures 1 to 5 The method for preparing the all-solid-state battery cell provided in the present application comprises the following steps:

[0038] S10, see Figure 1 and Figure 5 , positive electrode slurry is coated on two opposite sides of the positive electrode current collector 10 to form a positive electrode active layer 12 , thereby obtaining a positive electrode sheet 100 .

[0039] The positive electrode current collector 10 may be aluminum foil or carbon-coated aluminum foil.

[0040] The positive electrode slurry includes a positive electrode active material, a positive electrode conductor and a positive electrode binder. The positive electrode active material may be LiMPO4 or LiNO2, wherein M may be at least one of Fe, Co, Ni or Mn, and N may be at least one of Ni, Co, Mn or Al. As an example, the positive electrode active material may be lithium iron phosphate (LFP for short), lithium manganese iron phosphate (LMFP for short), lithium manganese oxide (LMO for short), lithium cobalt oxide (LCO for short), lithium nickel manganese oxide (LNMO for short), lithium nickel cobalt manganese oxide (NCM for short), lithium nickel cobalt aluminum oxide (NCA for short), etc.

[0041] The positive electrode binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin. The positive electrode conductor may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon fibers.

[0042] The thickness of the positive electrode sheet 100 may be 85 to 200 μm. For example, the thickness of the positive electrode sheet 100 may be 100 μm or 190 μm.

[0043] It should be noted that the coating method in the embodiments of the present application can be dry coating or wet coating.

[0044] When dry coating is adopted, the positive electrode slurry is sprayed on the surfaces of both sides of the positive electrode current collector 10 respectively, and then hot pressed to form the positive electrode active layer 12, and finally rolled to obtain the positive electrode sheet 100.

[0045] When wet coating is adopted, the positive electrode active material, positive electrode conductive agent and positive electrode binder are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry, and the positive electrode slurry is coated on both sides of the surface of the positive electrode collector 10. After drying, rolling and other processes, the positive electrode sheet 100 can be obtained.

[0046] S20, see Figure 2 and Figure 5 Under a protective atmosphere, electrolyte slurry is coated on two opposite sides of the lithium foil 20 to form a solid electrolyte layer 22 , thereby obtaining an electrolyte / lithium foil / electrolyte composite sheet 200 .

[0047] In some embodiments, the lithium foil 20 may be lithium metal or a lithium alloy, such as Li-In alloy, Li-Sn alloy, etc. The protective atmosphere includes at least one of argon, nitrogen, helium, neon, krypton or xenon.

[0048] As an example, the lithium foil 20 is a lithium metal foil, and the protective atmosphere is high-purity argon gas, which can fully isolate water and oxygen and prevent lithium metal from chemically reacting, thereby ensuring the performance of the lithium foil 20 .

[0049] In some embodiments, the thickness of the lithium foil 20 may be 20-100 μm. For example, the thickness of the lithium foil 20 is 20 μm, 35 μm, 50 μm, or 100 μm.

[0050] In some embodiments, before coating the electrolyte slurry on the two opposite sides of the lithium foil 20 , the process further includes: performing a plasma activation treatment on the lithium foil 20 under a protective atmosphere.

[0051] As an example, after the lithium foil 20 is activated from the storage bin, its surface is cleaned by Ar plasma in a high-purity argon protective atmosphere to remove the oxidative deterioration on the surface of the lithium foil 20 to complete the activation.

[0052] The electrolyte slurry may include at least one of a sulfide electrolyte or a halide electrolyte. As an example, the sulfide electrolyte may be Li2S-SiS2, thio-LISICON, Li 10 GeP2S 12 , Li2S-P2S5, Li6PS5Cl and Li2S-B2S3, etc. The halide electrolyte can be Li 2.5 Y 0.5 Zr 0.5 Cl6, Li3YCl6, Li3BrY6, Li3ErCl6, Li3ErI6 or Li3 YbCl6, etc.

[0053] In some embodiments, the electrolyte slurry may further include an electrolyte binder. As an example, the electrolyte binder may include at least one of polyvinylidene fluoride, styrene butadiene rubber (SBR), nitrile rubber (NBR), hydrogenated nitrile rubber (HNBR), styrene-butadiene-styrene block copolymer (SBS), styrene-ethylene-butylene-styrene block copolymer (SEBS), and polytetrafluoroethylene.

[0054] Similarly, the electrolyte slurry can be formed on the surface of the lithium foil 20 by wet coating or dry coating. When wet coating is adopted, the electrolyte slurry further includes a solvent, such as cyclohexanone.

[0055] In some embodiments, the thickness of the solid electrolyte layer 22 may be 25-70 μm. For example, the thickness of the solid electrolyte layer 22 may be 25 μm, 50 μm, 65 μm, etc.

[0056] S30, see Figure 3 , Figure 4 and Figure 5, the positive electrode sheets 100 and the electrolyte / lithium foil / electrolyte composite sheets 200 are alternately stacked to form an intermediate 300, and the intermediate 300 is subjected to isostatic pressing to obtain an all-solid-state battery cell 400.

[0057] In some embodiments, the alternating lamination step is performed under a protective atmosphere. Optionally, the protective atmosphere comprises at least one of argon, nitrogen, helium, neon, krypton or xenon.

[0058] Preferably, the entire production process of the embodiment of the present application is carried out under the protection of high-purity argon gas, so as to fully ensure the performance of the lithium foil 20 and reduce the dependence on the workshop production line environment.

[0059] In the embodiment of the present application, before the alternating stacking step, the positive electrode sheet 100 and the electrolyte / lithium foil / electrolyte composite sheet 200 are die-cut to uniformly cut into the required battery cell size.

[0060] In some embodiments, the isostatic pressing process may be cold isostatic pressing or warm isostatic pressing. In the embodiments of the present application, warm isostatic pressing is used, the temperature may be 30 to 120° C., and the pressure may be 50 to 550 MPa.

[0061] In some embodiments, after the isostatic pressing treatment, the steps further include: tab welding and battery cell shelling.

[0062] Among them, the tab welding can be ultrasonic welding.

[0063] In some embodiments, the two opposite outermost sides of the intermediate body 300 are positive electrode sheets 100, and before the intermediate body 300 is subjected to isostatic pressing, the following steps are further included:

[0064] An electrolyte / lithium foil composite sheet 30 is disposed on the surface of the outermost positive electrode sheet 100 of the intermediate body 300. The electrolyte / lithium foil composite sheet 30 includes a stacked outer lithium foil (not shown) and an outer solid electrolyte layer (not shown). A buffer material layer 32 is disposed on the surface of the outer lithium foil away from the solid electrolyte layer.

[0065] It can be understood that the electrolyte / lithium foil composite sheet 30 can be prepared by coating the electrolyte slurry on one side of the lithium foil 20 .

[0066] In some embodiments, the buffer material layer 32 includes at least one of a polyethylene oxide (PEO) film, a polyethylene naphthalate (PEN) film, and a polyphenylene sulfide (PPS) film. The buffer material layer 32 can prevent the electrode from contacting the battery cell housing 40, thereby improving safety.

[0067] In practical applications, see Figure 5Step S10 and step S20 can be performed symmetrically at the same time, and the production of the positive electrode sheet 100 and the electrolyte / lithium foil / electrolyte composite sheet 200 can be completed simultaneously in the large double-sided coating equipment. After the electrolyte / lithium foil composite sheet 30 and the buffer material layer 32 are packaged on the outermost side, the steps of drying, cutting, alternating lamination, ear welding, isostatic pressing, shell packaging, etc. can be uniformly performed, and finally a "Y"-shaped rapid assembly all-solid-state battery production line is realized. Compared with the traditional liquid production line, it can be compatible with many equipments and completely eliminates the processes of winding the diaphragm and injecting the liquid, realizing the synchronous innovation of the liquid battery from the manufacturing process.

[0068] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0069] Example 1

[0070] This embodiment provides an all-solid-state battery cell, and the preparation method thereof comprises the following steps:

[0071] (1) Preparation of positive electrode sheet: The positive electrode slurry is coated on the opposite sides of the carbon-coated aluminum foil positive electrode current collector by wet coating, and then dried to form a positive electrode active layer to obtain a positive electrode sheet. The positive electrode active slurry includes positive electrode active material lithium nickel cobalt manganese oxide (LiNi 0.8 Co 0.1 Mn 0.1 O2, NCM11), conductive agent vapor grown carbon fiber (VGCF) and binder polyvinylidene fluoride (PVDF), the thickness of the positive electrode active layer is 80μm, and the thickness of the prepared positive electrode sheet is 190μm.

[0072] (2) Preparation of electrolyte / lithium foil / electrolyte composite sheet: A lithium metal foil with a thickness of 35 μm was taken and subjected to argon plasma activation treatment in a high-purity argon protective atmosphere. Then, in a high-purity argon protective atmosphere (fully isolated from water and oxygen), a sulfide electrolyte was coated on the opposite sides of the lithium metal foil to form a Li6PS5Cl solid electrolyte layer with a thickness of 65 μm, thereby obtaining an electrolyte / lithium foil / electrolyte composite sheet.

[0073] (3) Preparation of all-solid-state battery cells: The positive electrode sheet and the electrolyte / lithium foil / electrolyte composite sheet are die-cut and alternately stacked to obtain an intermediate, and a single layer of electrolyte / lithium foil composite sheet and a buffer material layer are sequentially stacked on the opposite sides of the intermediate, and then the tabs are welded, warm isostatically pressed, and the battery cell is shelled to obtain an all-solid-state battery cell.

[0074] The all-solid-state battery cell is made into an all-solid-state battery through steps such as formation, and a cycle performance test is carried out at a current of 0.05C. The capacity retention rate can be maintained at 85% after 500 cycles.

[0075] In summary, the preparation method provided in this application can not only solve the problem of poor mechanical strength of the solid electrolyte layer and achieve compatibility with the liquid battery production line, but also greatly reduce the production process of all-solid-state batteries and improve production efficiency. The prepared all-solid-state batteries have good electrochemical properties.

[0076] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents the selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present application.

Claims

1. A method for preparing an all-solid-state battery cell, characterized in that: The following steps are involved: The positive electrode slurry is coated on two opposite sides of the positive electrode current collector to form a positive electrode active layer to obtain a positive electrode sheet; Under a protective atmosphere, coating electrolyte slurry on two opposite sides of the lithium foil to form a solid electrolyte layer, thereby obtaining an electrolyte / lithium foil / electrolyte composite sheet; The positive electrode sheets and the electrolyte / lithium foil / electrolyte composite sheets are alternately stacked to form an intermediate, and the intermediate is subjected to isostatic pressing to obtain an all-solid-state battery cell.

2. The preparation method according to claim 1, characterized in that: The lithium foil is lithium metal or lithium alloy; Optionally, the thickness of the lithium foil is 20-100 μm.

3. The preparation method according to claim 1 or 2, characterized in that: The electrolyte slurry includes at least one of a sulfide electrolyte or a halide electrolyte; Optionally, the solid electrolyte layer has a thickness of 25 to 70 μm.

4. The preparation method according to claim 1, characterized in that: The thickness of the positive electrode sheet is 85-200 μm.

5. The preparation method according to claim 1, characterized in that: Before coating the electrolyte slurry on the two opposite sides of the lithium foil respectively, the method further comprises: The lithium foil is subjected to a plasma activation treatment under a protective atmosphere.

6. The preparation method according to claim 1, characterized in that: The alternating lamination steps are performed under a protective atmosphere; Optionally, the protective atmosphere comprises at least one of argon, nitrogen, helium, neon, krypton or xenon.

7. The preparation method according to claim 1, characterized in that: The outermost layers on opposite sides of the intermediate body are the positive electrode sheets; Before the intermediate is subjected to isostatic pressing, the method further comprises: An electrolyte / lithium foil composite sheet is arranged on the surface of the positive electrode sheet at the outermost layer of the intermediate body. The electrolyte / lithium foil composite sheet includes a stacked outer lithium foil and an outer solid electrolyte layer. A buffer material layer is arranged on the surface of the outer lithium foil away from the outer solid electrolyte layer.

8. The preparation method according to claim 7, characterized in that: The buffer material layer includes at least one of a PEO film, a PEN film or a PPS film.

9. An all-solid-state battery cell, characterized in that: The preparation is obtained by the preparation method according to any one of claims 1 to 8.

10. An all-solid-state battery, characterized in that: Comprising the all-solid-state battery cell as claimed in claim 9.